IMPLEMENTASI MANAJEMEN DAKWAH DALAM PEMBINAAN AKHLAK MAHASANTRI PUTRI PONDOK PESANTREN AL-LATHIFIYYAH PALEMBANG - Margareta Comala Sari; Hidayat HT; Anang Walian (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of da'wah management in the moral development of female mahasantri at Al-Lathifiyyah Islamic Boarding School, Palembang, and to identify the supporting and inhibiting factors in the implementation of moral development, particularly regarding the supervision of the consistency of Qur’anic moral practices when the mahasantri are outside the boarding school environment. This research employed a qualitative approach using a field research design. Data were collected through interviews, observations, and documentation involving caregivers, female religious instructors (ustadzah), administrators, and female mahasantri of Al-Lathifiyyah Islamic Boarding School, Palembang. The findings reveal that the implementation of da'wah management in the moral development of female mahasantri has been carried out through management functions consisting of planning, organizing, implementing, and supervising. The planning stage was conducted through the formulation of moral development programs based on Qur’anic values and religious activities. Organizing was implemented through a clear distribution of responsibilities among caregivers, ustadzah, and boarding school administrators. The implementation of moral development was realized through the habituation of worship practices, religious studies, discipline enforcement, and exemplary role modeling in daily life. Supervision was carried out through monitoring daily activities, conducting periodic evaluations, and providing continuous guidance to the mahasantri. The supporting factors in moral development include the exemplary conduct of mentors, a conducive boarding school environment, regular religious activities, and a well-structured management system. Meanwhile, the inhibiting factors include differences in the students’ backgrounds, external environmental influences, uncontrolled use of technology and social media, and limited supervision when the mahasantri are outside the boarding school environment. Nevertheless, these challenges are addressed through persuasive, communicative, and sustainable coaching approaches.